The genetic basis of parental care evolution in monogamous mice - Bendesky, Andres; Kwon, Young-Mi; Lassance, Jean-Marc; Lewarch, Caitlin L.; Yao, Shenqin; Peterson, Brant K.; He, Meng Xiao; Dulac, Catherine; Hoekstra, Hopi E. (Nature (London), 2017)
Parental care is essential for the survival of mammals, yet the mechanisms underlying its evolution remain largely unknown. Here we show that two sister species of mice, Peromyscus polionotus and Peromyscus maniculatus , have large and heritable differences in parental behaviour. Using quantitative genetics, we identify 12 genomic regions that affect parental care, 8 of which have sex-specific effects, suggesting that parental care can evolve independently in males and females. Furthermore, some regions affect parental care broadly, whereas others affect specific behaviours, such as nest building. Of the genes linked to differences in nest-building behaviour, vasopressin is differentially expressed in the hypothalamus of the two species, with increased levels associated with less nest building. Using pharmacology in Peromyscus and chemogenetics in Mus , we show that vasopressin inhibits nest building but not other parental behaviours. Together, our results indicate that variation in an ancient neuropeptide contributes to interspecific differences in parental care. Parental care in mice evolves through multiple genetic changes; one candidate is vasopressin, the reduced expression of which promotes parental nest-building behaviour in monogamous mice. Genetics of parental care Rodents display a wide range of parental care behaviours, such as nest building, with some species more driven to perform these duties than others. However, the genetic and evolutionary mechanisms that influence the extent to which parental care behaviours are performed have remained unknown. Here, Hopi Hoekstra and colleagues utilize a quantitative genetic approach to identify genetic candidates that influence parental care in closely related mouse species. Genetic changes that enhance the levels of the hypothalamic hormone vasopressin were linked to less nest building. In addition, artificial manipulation of neurons releasing vasopressin could directly affect the extent of nest building, with lower vasopressin-releasing neuronal activity correlated with increased levels of nest building. This suggests that variation in neuropeptide signalling may contribute to complex social behaviours such as parental care.